Interest rate versus profit rate in the light of Islamic maxim: al-ibratu fil uqūdi lil maqāsidi wa ma’ānī lā lil alfāzi wal mabani/ Saheed Abdullahi Busari, Haruna Babatunde Jaiyeoba and Mohamad Sabri Zakaria - Busar, Saheed Abdullahi; Jaiyeoba, Haruna Babatunde; Zakaria, Mohamad Sabri (Universiti Teknologi MARA Selangor, 2022)
The concept of interest and profit is as old as the history of commercial transactions because, in Jahiliyyah (ignorant) period, people transact business based on interest and sometimes for profit. These concepts are also not alien to conventional financial practice, except that many people cannot distinguish between interest-based and profit-based transactions. As much as shariah encouraged commercial transactions of common and fair benefit through exchanging commodities and money, it equally emphasised the need for fair play and justice for entire market stakeholders. This study aims to explore and explicates literature on the differences between conventional bank interest rates and the Islamic bank profit rate in financing. The study will describe the contractual pictures of both methodologies to analyse the convergent and divergent features between interest-based loans and profit-based financing. This study uses the Islamic legal maxim theory of "In contracts, the effect is given to intention and meaning and not words and forms" (Al-‘ibratu fil uqūdi lil maqāsidi wal ma’ānī lā lil alfāzi wal mabānī) as a fundamental principle in determining shariah compliant profit based in commercial transactions. This study arrived at findings on the distinctive divergent between the interest rate and profit rates in financing. The study identifies issues those convergent trigger concerns among researchers and critiques in contemporary applications can be resolved based on contractual intent and meaning rather than words and forms. This study came up with recommendations for improving the operational status of Islamic financial transactions in the profit rate.